Implementation of the Value Religious Moderation by Students in the Learning Process in Higher Education - Hasanah Dilia, Muqita Hanifah; Slam, Zaenul (Department of Civic Education, 2023)
Indonesia is a multicultural nation. It has a very diverse diversity of religions, cultures, languages, tribes, traditions. In this condition, Indonesia is very prone to disunity. Therefore, this research aims to discuss the importance of implementing religious moderation values based on Pancasila values. Students must have a critical thinking pattern so that students are able to distinguish the right understanding for multicultural conditions like this. Thus Indonesia will avoid divisions and various kinds of religious moderation. The right understanding will lead to high awareness of the application of Pancasila values related to this moderation. So that students can have a high awareness of the importance of understanding religious moderation. The method used is descriptive qualitative. The conclusion of this research is that a diverse life in order to remain harmonious, each community must have the right attitude for multicultural conditions. The right attitude is to be tolerant, respect differences, and not impose the will with violence.